2019
DOI: 10.1093/mnras/stz1940
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional dust mapping of 12 supernovae remnants in the Galactic anticentre

Abstract: We present three dimensional (3D) dust mapping of 12 supernova remnants (SNRs) in the Galactic anti-center (Galactic longitude l between 150 • and 210 • ) based on a recent 3D interstellar extinction map. The dust distribution of the regions which cover the full extents in the radio continuum for the individual SNRs are discussed. Four SNRs show significant spatial coincidences between molecular clouds (MCs) revealed from the 3D extinction mapping and the corresponding radio features. The results confirm the i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 60 publications
9
31
0
Order By: Relevance
“…It was assumed that these objects are interacting (see Xiao & Zhu 2012, and references therein). However, two new estimates of the distance to the SNR appeared recently: Zhao et al (2018) obtained 1.98 kpc (and 1.55 kpc to the Rosette Nebula) while Yu et al (2019) derived 0.94 or 1.26 kpc. These new estimates are apparently not consistent with the idea of any interaction between the remnant and the nebula.…”
Section: Diffuse Emissionmentioning
confidence: 99%
“…It was assumed that these objects are interacting (see Xiao & Zhu 2012, and references therein). However, two new estimates of the distance to the SNR appeared recently: Zhao et al (2018) obtained 1.98 kpc (and 1.55 kpc to the Rosette Nebula) while Yu et al (2019) derived 0.94 or 1.26 kpc. These new estimates are apparently not consistent with the idea of any interaction between the remnant and the nebula.…”
Section: Diffuse Emissionmentioning
confidence: 99%
“…Galactic SNRs are mostly observed in the radio domain, and the updated version of Galactic SNR catalog (Green 2019) lists 294 objects, where only a part of the observed sample actually has their distance determined from some independent empirical method (Green 1984). Some of the methods for the SNR distance determination include: coincidences with the observed H ii regions and molecular clouds (Eger et al 2011, Ranasinghe and Leahy 2018a, 2018b, Supan et al 2018, Yu et al 2019, H i absorption features and polarization (Yar-Uyanker et al 2004, Ranasinghe and Leahy 2018a, 2018b, association with the red clump stars (Shan et al 2018(Shan et al , 2019, pulsars (Chatterjee et al 2009), the optical proper motion and Hα line radial velocity measurements (Lozinskaya et al 1993, etc. When distance determination is not possible by using some of the above mentioned methods, some estimates can be inferred using the radio-surfacebrightness-to-diameter (Σ -D) relation, first proposed by Shklovsky (1960):…”
Section: Introductionmentioning
confidence: 99%
“…The Monoceros Loop is one of the largest (Θ = 220 ′ ) and probably the oldest SNRs of our sample, although the age determination is very uncertain (30–150 kyr, Welsh et al 2001). From Ferrand & Safi‐Harb (2012), we adopted d = 1.44 ± 0.54 kpc as recent works (Yu et al 2019; Zhao et al 2018) place it at d=0.9410.094+0.096 kpc or d=1.2570.101+0.092 kpc and d = 1.98 kpc, respectively. The discrepancy is connected to the question of whether the Monoceros Loop interacts with the Rosette Nebula (3C 163), an H II region bordering the SNR at the southwestern edge.…”
Section: Discussionmentioning
confidence: 99%
“…The Monoceros Loop is one of the largest (Θ = 220 ′ ) and probably the oldest SNRs of our sample, although the age determination is very uncertain (30-150 kyr, Welsh et al 2001). From Ferrand & Safi-Harb (2012, we adopted d = 1.44 ± 0.54 kpc as recent works (Yu et al 2019;Zhao et al 2018) We observed 21 stars with UVES/VLT in the Monoceros Loop, where no associated neutron star is known. Eight of those were ruled out because they were found to be giants.…”
Section: Monoceros Loopmentioning
confidence: 99%
See 1 more Smart Citation